Sulfamethoxazole derivatives complexed with metals: a new alternative against biofilms of rapidly growing mycobacteria. Issue 8 (14th September 2018) - Siqueira, Fallon dos Santos; Rossi, Grazielle Guidolin; Machado, Alencar Kolinski; Alves, Camilla Filippi Santos; Flores, Vanessa Costa; Somavilla, Viviane Drescher; Agertt, Vanessa Albertina; Siqueira, Josiéli Demetrio; Dias, Renne de Sousa; Copetti, Priscila Marquezan; Sagrillo, Michele Rorato; Back, Davi Fernando; et al.
Abstract: Biofilms are considered important sources of infections on biomedical surfaces, and most infections involving biofilm formation are associated with medical device implants. Therefore, there is an urgent need for new antimicrobial compounds that can combat microbial resistance associated with biofilm formation. In this context, this work aimed to evaluate the antibiofilm action of sulfamethoxazole complexed with Au, Cd, Cu, Ni and Hg on rapidly growing mycobacteria (RGM), as well as to evaluate their safety through cytotoxic assays. The results demonstrate potentiation of the novel compounds in antibiofilm activity, mainly in the complex with Au, which was able to completely inhibit biofilm formation and had the capacity to destroy the biofilm at all the concentrations tested. All cytotoxic data suggest that the majority of sulfamethoxazole metallic derivatives are antimicrobial alternatives, as well as safe molecules, which could be used as potential therapeutic agents for bacterial and biofilm elimination.